Exploring The Use of Generative Artificial Intelligence to Support Digital Literacy Among Early Childhood Teachers - Virdaus, Varia Virdania; Rofiyarti, Fitri; Agustina, Amelia Greceta Tiara (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2026)
The rapid development of generative artificial intelligence (AI) has transformed educational practices, creating new opportunities for teachers to enhance their professional competencies, particularly in digital literacy. However, existing research has largely focused on higher education contexts, with limited attention given to early childhood education teachers. This study aims to explore how early childhood education teachers utilize generative artificial intelligence to support digital literacy in their teaching practices. This study employed a qualitative exploratory approach involving 18 early childhood education teachers with experience in using generative AI tools. Data were collected through semi-structured interviews, open-ended questionnaires, and reflective responses. The data were analyzed using inductive thematic analysis to identify patterns of use, perceived benefits, and challenges in integrating generative AI into teaching practices. The findings reveal that teachers use generative AI in multiple ways, including instructional preparation, idea generation, information search, and digital communication. These practices contribute to the development of teachers’ digital literacy, particularly in content creation, creative engagement, information evaluation, and ethical awareness. At the same time, teachers experience challenges related to the accuracy of AI-generated content, ethical considerations, and the need to maintain professional judgment. This study contributes to the growing discourse on artificial intelligence in education by highlighting the role of generative AI as a supportive tool for enhancing teachers’ digital literacy in early childhood education. The findings emphasize that digital literacy in the AI era requires not only technical skills but also reflective and critical engagement with technology.